2018
DOI: 10.1111/imr.12656
|View full text |Cite
|
Sign up to set email alerts
|

Immunological memories of the bone marrow

Abstract: SummaryMemory for antigens once encountered is a hallmark of the immune system of vertebrates, providing us with an immunity adapted to pathogens of our environment. Despite its fundamental relevance, the cells and genes representing immunological memory are still poorly understood. Here we discuss the concept of a circulating, proliferating, and ubiquitous population of effector lymphocytes vs concepts of resting and dormant populations of dedicated memory lymphocytes, distinct from effector lymphocytes and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 185 publications
(375 reference statements)
2
74
0
Order By: Relevance
“…Antigen-specific memory provided by the adaptive immune system is multi-layered. Antibodies secreted by memory plasma cells provide immediate protection, while memory T and B lymphocytes provide reactive memory against excessive or modified antigen [9,30]. Moreover, immune memory cells are compartmentalized in various tissues [9,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antigen-specific memory provided by the adaptive immune system is multi-layered. Antibodies secreted by memory plasma cells provide immediate protection, while memory T and B lymphocytes provide reactive memory against excessive or modified antigen [9,30]. Moreover, immune memory cells are compartmentalized in various tissues [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies secreted by memory plasma cells provide immediate protection, while memory T and B lymphocytes provide reactive memory against excessive or modified antigen [9,30]. Moreover, immune memory cells are compartmentalized in various tissues [9,31]. We have previously shown that prominent populations of memory plasma cells and memory CD4 + and CD8 + T lymphocytes reside and rest in the bone marrow [7,8,11,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-lived memory plasma cells persist for a lifetime in mice (Manz, Thiel, & Radbruch, 1997;Slifka, Antia, Whitmire, & Ahmed, 1998), non-human primates (Hammarlund et al, 2017) and in humans (Landsverk et al, 2017). They form an independent population of memory cells (Chang, Tokoyoda, & Radbruch, 2018;Radbruch et al, 2006). Memory plasma cells are evenly distributed throughout the bone marrow and most if not all of them directly contact a mesenchymal stromal cell (Zehentmeier et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While the generation of memory B lymphocytes and their role in secondary immune responses has been subject of intense research, little is known about their maintenance over time in the apparent absence of antigen. For memory T lymphocytes, relatively new research has unveiled a highly structured organization of their maintenance, describing populations of 225 circulating and tissue-resident memory T cells (Trm)2 . Trm have been described for nearly all organs investigated, including the BM6, 7,29 .…”
mentioning
confidence: 99%